Cestode parasites release extracellular vesicles with microRNAs and immunodiagnostic protein cargo - Ancarola, María Eugenia (2017)
Intercellular communication is crucial in multiple aspects of cell biology. This interaction can be mediated by several mechanisms including extracellular vesicle (EV) transfer. EV secretion by parasites has been reported in protozoans, trematodes and nematodes. Here we report that this mechanism is present in three different species of cestodes, Taenia crassiceps, Mesocestoides corti and Echinococcus multilocularis. To confirm this we determined, in vitro, the presence of EVs in culture supernatants by transmission electron microscopy. Interestingly, while T. crassiceps and M. corti metacestodes secrete membranous structures into the culture media, similar vesicles were observed in the interface of the germinal and laminated layers of E. multilocularis metacestodes and were hardly detected in culture supernatants. We then determined the protein cargo in the EV-enriched secreted fractions of T. crassiceps and M. corti conditioned media by LC-MS/MS. Among the identified proteins, eukaryotic vesicle-enriched proteins were identified as expected, but also proteins used for cestode disease diagnosis, proteins related to neurotransmission, lipid binding proteins as well as host immunoglobulins and complement factors. Finally, we confirmed by capillary electrophoresis the presence of intravesicular RNA for both parasites and detected microRNAs by reverse transcription-PCR. This is the first report of EV secretion in cestode parasites and of an RNA secretion mechanism. These findings will provide valuable data not only for basic cestode biology but also for the rational search for new diagnostic targets.